Devil's Advocate for Werewolf in Epaulets: What Kind of Lawyers Defend Misconducted Law Enforcers in Russian Courts? - Anton P. Kazun (Žurnal Institucionalʹnyh Issledovanij, 2018)
If the rule of law does not prevail, certain privileged groups gain an advantage in court. Recent studies have shown that law enforcers in Russia are one of the social groups, which, being be explained in different ways, including their special status and loyalty of the judges. Without rejecting these possible reasons, we assume that law enforcement officers, having a unique experience within the law enforcement system, are able to choose for themselves more effective criminal attorneys. Based on a survey of 3,317 attorneys, we show the difference of ethics and effectiveness of lawyers who have or do not have the experience of protecting law enforcers and judges. Attorneys of law enforcers often had working experience in the law enforcement system. Such lawyers achieve more significant results in conditions of "accusatory bias". In addition, they more often record violations of the rights of defendants, more often achieve positive results for their clients. Finally, the defenders of law enforcers are often "devil's advocates" as they declare their willingness to protect the interests of people who enjoy the reputation of mafia.